High posttransplant cancer incidence in renal transplanted patients with pretransplant cancer - Hellström, Vivan; Döhler, Bernd (Transplantation, 2017)
Background: Patients with previous cancer have increasingly been accepted for renal transplantation. Posttransplant cancer risk and survival rates of these patients are unknown. Our objective was to assess the risk of posttransplant cancer in this patient group. Methods: In this retrospective, nested case-control study, we assessed the outcome of all (n = 95) renal transplanted patients with pretransplant cancer diagnoses in the Uppsala-Örebro region, Sweden. The control group was obtained from the Collaborative Transplant Study registry and included European patients without pretransplant cancer. The other control group comprised the entire renal transplanted population in Uppsala. Development of recurrent cancer, de novo cancer, and patient survival were determined. Results: Patients with pretransplant cancer showed higher incidence of posttransplant cancers and shorter survival compared with the control groups (P < 0.001). No obvious pattern in malignant diagnoses was observed. Death-censored graft survival was unaffected. Conclusions: Despite previously adequate cancer treatments and favorable prognoses, almost half of the patients experienced a posttransplant cancer. These observations do not justify abstaining from transplanting all patients with previous malignancies, because more than 50% of the patients survive 10 years posttransplantation. A careful oncological surveillance pretransplant as well as posttransplant is recommended.
Gesehen am 26.04.2018